Spatial resilience of the Great Barrier Reef under cumulative disturbance impacts. (6th May 2019) - Mellin, Camille; Matthews, Samuel; Anthony, Kenneth R.N.; Brown, Stuart C.; Caley, M. Julian; Johns, Kerryn A.; Osborne, Kate; Puotinen, Marjetta; Thompson, Angus; Wolff, Nicholas H.; Fordham, Damien A.; MacNeil, M. Aaron
Abstract: In the face of increasing cumulative effects from human and natural disturbances, sustaining coral reefs will require a deeper understanding of the drivers of coral resilience in space and time. Here we develop a high‐resolution, spatially explicit model of coral dynamics on Australia's Great Barrier Reef (GBR). Our model accounts for biological, ecological and environmental processes, as well as spatial variation in water quality and the cumulative effects of coral diseases, bleaching, outbreaks of crown‐of‐thorns starfish ( Acanthaster cf. solaris ), and tropical cyclones. Our projections reconstruct coral cover trajectories between 1996 and 2017 over a total reef area of 14, 780 km 2, predicting a mean annual coral loss of −0.67%/year mostly due to the impact of cyclones, followed by starfish outbreaks and coral bleaching. Coral growth rate was the highest for outer shelf coral communities characterized by digitate and tabulate Acropora spp. and exposed to low seasonal variations in salinity and sea surface temperature, and the lowest for inner‐shelf communities exposed to reduced water quality. We show that coral resilience (defined as the net effect of resistance and recovery following disturbance) was negatively related to the frequency of river plume conditions, and to reef accessibility to a lesser extent. Surprisingly, reef resilience was substantially lower within no‐take marine protected areas, however this difference was mostly driven by the effect of water quality. Our model provides a new validated, spatially explicit platform for identifying the reefs that face the greatest risk of biodiversity loss, and those that have the highest chances to persist under increasing disturbance regimes. Abstract : In this study, we develop a spatially explicit model of coral cover that accounts for the cumulative impact of multiple disturbances from 1998 to 2017 across Australia's Great Barrier Reef. We identify the environmental drivers of coral growth for six major benthic communities, as well as anthropogenic correlates of reef resilience.